1 Proceedings and Acts of the General Assembly of Maryland 77 (William Hand Browne ed., 1883) - (:unkn) unknown (My University, 1639)
That every house keeper or housekeepers within this Province shall have ready continually upon all occasions within his her or their house for him or themselves and for every person within his her or their house able to bear armes one Serviceable fixed gunne of bastard muskett boare one pair of bandeleers or shott bagg one pound of good powder foure pound of pistol or muskett shott and Sufficient quantity of match for match locks and of flints for firelocks and before Christmas next shall also find a Sword and Belt for every such person as aforesaid. Further, "every householder of every hundred haveing in his family three men or more able to beare armes shall Send one man completely armed for every such three men and two men for every five and so proportionately.
Keywords: MILITIAS; REQUIRED POSSESSION